ANALYSIS OF THE USE OF MOBILE APPLICATIONS BY FOREIGN AND UKRAINIAN PHARMACIES WITHIN THE CONCEPT OF HOLISTIC MARKETING - Sakhnatska , Nataliia; Aliekperova , Nataliia (The Ukrainian Scientific Medical Youth Journal, 2021)
digitalization of the pharmaceutical sector requires the use of modern marketing approaches to provide pharmacies with quality and safe pharmaceutical care within the holistic concept of marketing management. A promising direction of digital transformation of the retail market of medicines is the introduction of special mobile applications in the activities of pharmacies, which become a safe and accessible platform for the sale of medicines to the population.The main purpose of the study is to exercise the analysis of the features of pharmaceutical services provision using mobile applications to foreign and Ukrainian pharmacy chains. The study is based on the use of content analysis, analysis of electronic resources, system, and logical analysis, as well as of the modeling method.As the objects of the study, American pharmacy chains CVS Pharmacy and Walgreens, British Boots, and Lloyds Pharmacy were selected, as well as 10 pharmacy chains in Ukraine in terms of turnover in January-October 2020.It is revealed that the leading world leaders in the retail market of medicines have been using this digital tool in their marketing activities for a long time. Unlike domestic pharmacies, applications of foreign pharmacies additionally provide such services as online registration for testing and vaccination against COVID-19, additional opportunities for the visually impaired, drug disposal, and others. Among the studied Ukrainian pharmacy chains by market share, only a half have mobile applications with various functions, among the most developed mobile applications are “Like” from LLC “Apteka-Magnolia” (“Pharmacy-Magnolia”), "Pharmacy 911" and “Apteka Dobroho Dnia” (“Good Afternoon Pharmacy”).An integrated model of a mobile application of a modern pharmacy has been developed, aimed at effective interaction of all necessary functions to provide the population with high-quality, convenient, and available pharmaceutical care. Promising areas of further research are the justification of the feasibility of using certain functions of mobile applications, as well as other digital tools, such as pharmacy websites, social media pages within the concept of holistic marketing.The results of the study conducted may be useful to specialists in the pharmaceutical industry for use in practical pharmacy.